2010
DOI: 10.1128/mcb.00601-09
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-Activated S6K1 Phosphorylates Rictor on Threonine 1135 and Regulates mTORC2 Signaling

Abstract: The mammalian target of rapamycin (mTOR) is a conserved Ser/Thr kinase that forms two functionally distinct complexes important for nutrient and growth factor signaling. While mTOR complex 1 (mTORC1) regulates mRNA translation and ribosome biogenesis, mTORC2 plays an important role in the phosphorylation and subsequent activation of Akt. Interestingly, mTORC1 negatively regulates Akt activation, but whether mTORC1 signaling directly targets mTORC2 remains unknown. Here we show that growth factors promote the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
323
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(356 citation statements)
references
References 83 publications
25
323
2
2
Order By: Relevance
“…Concerning intracellular localization, nuclear-in addition to cytoplasmicp-mTOR reaction was observed in o5% of the cells in our study and we did not attribute this to mTORC2 activity-especially because Rictor (an element of the mTORC2 complex) was present only in the cytoplasm, as functionally expected and reported also by others. 23 One of the key targets of mTORC2 is Akt. 23 Akt has been reported to show activity in about 30-40% of diffuse large B-cell lymphoma cases, 24,25 which is in the same range as overall Rictor expression in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning intracellular localization, nuclear-in addition to cytoplasmicp-mTOR reaction was observed in o5% of the cells in our study and we did not attribute this to mTORC2 activity-especially because Rictor (an element of the mTORC2 complex) was present only in the cytoplasm, as functionally expected and reported also by others. 23 One of the key targets of mTORC2 is Akt. 23 Akt has been reported to show activity in about 30-40% of diffuse large B-cell lymphoma cases, 24,25 which is in the same range as overall Rictor expression in our study.…”
Section: Discussionmentioning
confidence: 99%
“…23 One of the key targets of mTORC2 is Akt. 23 Akt has been reported to show activity in about 30-40% of diffuse large B-cell lymphoma cases, 24,25 which is in the same range as overall Rictor expression in our study. Rictor expression and Akt activity may explain the inefficiency of rapamycin analog (rapalog) therapy in recent phase I/II studies, where targeting mTORC1 resulted in 28-32% response rates in high-grade lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, la phosphorylation des protéines adaptatrices IRS (insulin receptor substrate 1) par mTORC1 et S6K a pour effet de diminuer leur stabilité et d'empêcher le recrutement de PI3K [25]. De plus, des étu-des plus récentes ont démontré que Rictor est phosphorylé par S6K1, ce qui inhibe l'activité de mTORC2 et diminue la phosphorylation et l'activation d'Akt [26][27][28].…”
Section: Régulation De L'activité De Mtorc2unclassified
“…Previous studies have revealed that S6K1 phosphorylates rictor and SIN1 thereby negatively regulating mTORC2 activity [11,12]. Therefore, treatment with rapamycin or downregulation of raptor and S6K1 may paradoxically activate mTORC2.…”
Section: Mtorc2 Promotes Rapamycin-and Ligand-induced Igf-ir/insr Phomentioning
confidence: 99%
“…In addition, mTORC2 was shown to regulate protein kinase Cα and serum/ glucocorticoid-induced protein kinase 1 [8,9]. Recently, it has been found that mTORC1 and its downstream effector S6K1 negatively regulate mTORC2 via the phosphorylation of rictor and SIN1 [10][11][12], suggesting a regulatory link between these two complexes. In addition, prolonged treatment with rapamycin, an antibiotic product that predominantly inhibits mTORC1, leads to ERK1/2 phosphorylation [13].…”
Section: Introductionmentioning
confidence: 99%